2000
DOI: 10.1099/00221287-146-9-2219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for resistance to the anticancer drug cisplatin in Dictyostelium The GenBank accession numbers for the sequences reported in this paper are AF233610 (S-1-P lyase), AF233612 (PIP5K), AF233611 (P2Y purine receptor 1), AF233613 (CAAX prenyl protease) and AF233614 (unidentified gene).

Abstract: The efficacy of the widely used chemotherapeutic drug cisplatin is limited by the occurrence of drug-resistant tumour cells. To fully exploit the potential of this drug in cancer therapy, it is imperative to understand the molecular basis of cisplatin resistance. Using an insertional mutagenesis technique in cells of Dictyostelium discoideum, we have identified six genes which are involved in cisplatin resistance. None of these genes has been previously linked to resistance to this drug. Several of these genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 54 publications
10
50
0
Order By: Relevance
“…The upstream region, presumably containing expression regulatory elements, was confirmed by PCR amplification using fp1 and rp1 and partial sequencing. cis4c was previously shown by Northern blot analysis to be expressed throughout the life cycle (27).…”
Section: Architecture Of the Predicted Pp ␣-Glcnac-t2mentioning
confidence: 99%
See 4 more Smart Citations
“…The upstream region, presumably containing expression regulatory elements, was confirmed by PCR amplification using fp1 and rp1 and partial sequencing. cis4c was previously shown by Northern blot analysis to be expressed throughout the life cycle (27).…”
Section: Architecture Of the Predicted Pp ␣-Glcnac-t2mentioning
confidence: 99%
“…A cloned ClaI-ClaI fragment of Dictyostelium gDNA, known as cis4c, was found that had been isolated in a screen for genes that when disrupted resulted in increased resistance to the drug cisplatin (27). The sequence comprised a single long ORF, which conceptually encodes a polypeptide sequence that includes a 284-amino acid stretch with 29% identity and 52% similarity to that of the apparent catalytic domain of pp ␣-GlcNAc-T1 (Fig.…”
Section: Architecture Of the Predicted Pp ␣-Glcnac-t2mentioning
confidence: 99%
See 3 more Smart Citations